Emblica officinalis Fruit Pulp Extract Protects against Naproxen-Induced Gastric Ulcer in Rats: Anti-inflammatory and Antioxidant Machinery - Eman A. Abduljawad, Zuhair M. Mohammedsaleh (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The use of non-steroidal anti-inflammatory drugs (NSAIDs) is one of the leading causes of peptic ulcers. There is a rising interest and demand for nontoxic, antiulcer remedies derived from medicinal plants to treat NSAID-induced gastric ulcers (GU). Aim: This study is a comparative assessment of the possible gastro-protective role of Emblica officinalis fruit pulp extract (EOFPE) and Omeprazole (Omepra) against Naproxin (Naprox)-induced GU. Methodology: Five groups of rats (8 rats each) represent control, Naprox, Omepra (20 mg/kg), EOFPE (700 mg/kg), and EOFPE + Omepra. Omepra and EOFPE were ingested orally for 17 days. Naprox was ingested orally on day 15 for three consecutive days. Results: Pretreatment with EOFPE and/or Omepra caused significant increases in gastric pH and gastric mucin content. Besides, significant decline in the total gastric acidity and gastric mucosal lesion relative to the Naprox group. Pretreatment with EOFPE and/or Omepra markedly improved the examined gastric pathologic features in Naprox-pretreated groups. Besides, EOFPE and/or Omepra overcome the gastric inflammation and oxidative stress markers induced by Naprox ingestion. Pretreatment with both EOFPE + Omepra leads to the best antiulcer impact and lesion inhibition percent relative to the Naprox groups pretreated with either EOFPE or Omepra alone. Conclusion: EOFPE protected against Naprox-induced GU across anti-inflammatory and antioxidant mechanisms.